Aseptic Packaging - Djumarman Djumarman (Jurnal Kimia dan Kemasan, 1977)
The choice of a packaging material for a particular product raises a number of im portant considerations. The term aseptic packaging here is refer to conditions· sufficiently controlled that viable microbiological contamination of a product during packaging does not occur or is within practical limits for the subsequent usual comercial storage and distribution. This means that occasionally a very low level of contamination from the container or airbone sources may occur but does not result in spoilage.